EPEN-24. YAP1 FUSION PROTEINS MEDIATE ONCOGENIC ACTIVITY IN EPENDYMOMA VIA INTERACTION WITH TEAD TRANSCRIPTION FACTORS. Issue 2 (22nd June 2018) - Pajtler, Kristian W; Okonechnikov, Konstantin; Vouri, Mikaella; Brabetz, Sebastian; Jones, David T W; Korshunov, Andrey; Capper, David; Chavez, Lukas; Pfister, Stefan M; Kool, Marcel; Kawauchi, Daisuke
Abstract: In a previous study we identified two molecular groups of supratentorial (ST) ependymoma in pediatric patients driven by distinct gene fusions involving either the NF-κB effector RELA or the HIPPO signaling regulator YAP1, designated ST-EPN-RELA and ST-EPN-YAP1, respectively. The lack of adequate models for ST-EPN-YAP1, which predominantly occurs in very young children, has so far hindered the development of effective targeted therapies for these tumors. In an attempt to model this group, the most frequent fusion type, YAP1-MAMLD1, was cloned into a Luciferase-carrying transposable vector. Oncogenicity was subsequently tested using an electroporation-based in vivo gene transfer approach following injection of the vector into the lateral ventricle of E13.5 wildtype mouse embryos. After birth, YAP1-MAMLD1-expressing tumors, monitored using luciferase-based in vivo bioluminescence imaging, developed rapidly with 100% penetrance, indicating that the fusion alone is sufficient to initiate tumors. To further investigate the role of this fusion in human EPNs, we performed YAP1 ChIP-seq analyses on human ST-EPN-YAP1 and ST-EPN-RELA primary tumors. Despite similar gene expression levels of YAP1 in both molecular groups, our comparative analyses found that putative binding sites of TEADs, transcriptional factors interacting with YAP1, were significantly enriched in ST-EPN-YAP1-specific YAP1 target sites. In vivo validation further confirmed that interaction between YAP1-MAMLD1 and TEADs is crucial for oncogenicity of the fusion, since prevention of YAP1-TEAD binding did not result in tumor formation. Thus, targeting the YAP1-TEAD interaction might represent a promising therapeutic approach for this devastating infant disease.